Anthelmintic Potential of Medicinal Plants against Ancylostoma caninum - Savira Ekawardhani; Utari T. Anggoro; Ita Krissanti (Veterinary Medicine International)
Ancylostoma caninum is one of the most important hookworms in dogs. A study revealed that the prevalence of ancylostomiasis in Indonesia is relatively high. However, cases of persistent ancylostomiasis in dogs were reported, indicating the possibility of anthelmintic resistance. The aim of this review is to provide an overview of the anthelmintic potential of plants preclinically against A. caninum based on related research articles. This review retrieved 14 articles from 2001 to 2021 investigating 19 different plants. Momordica charantia, Diospyros anisandra, and Citrus aurantiifolia hold a promising prospect as anthelmintic against A. caninum. This review found aspects of those medicinal plants that need to be investigated deeper to improve our understanding of the matter. In vitro results in this review have not yet been tested in in vivo trials, which are essential in determining the efficacy and safety of the use of these medicinal plants and also to justify its clinical application.